Bridget D. Samuels: Phonological architecture: a biolinguistic perspective - Iosad, Pavel (Norsk Lingvistisk Tidsskrift, 2013)
The aim of Bridget D. Samuels' ambitious book, published in the series Oxford Studies in Biolinguistics, is to sketch a theory of phonological competence that is consistent with recent Minimalist thinking in syntax in postulating a simple but powerful computational core supplemented by extraphonological considerations ranging from the contingencies of acquisition and diachrony to a well-elaborated theory of the phonology-morphosyntax interface. She succeeds admirably in presenting a case for phonology as a component of the human linguistic capacity that lacks significant architectural differences vis-ÃƒÂƒ -vis other cognitive abilities involved in language (for contrasting views of phonology in this respect, cf. Bromberger & Halle 1989, Burton-Roberts 2000).